2019
DOI: 10.1187/cbe.18-12-0240
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Cognitive Science and Discipline-Based Education Research in the Undergraduate Science Classroom

Abstract: Cognitive science research on learning and instruction is often not directly connected to discipline-based research. In an effort to narrow this gap, this essay integrates research from both fields on five learning and instruction strategies: active retrieval, distributed (spaced) learning, dual coding, concrete examples, and feedback and assessment. These strategies can significantly enhance the effectiveness of science instruction, but they typically do not find their way into the undergraduate classroom. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
(95 reference statements)
2
12
0
Order By: Relevance
“…For example, Bevilacqua et al (2019) revealed that students who reported greater social closeness to their teacher showed higher brain-to-brain synchrony with the teacher, and this predicted cognitive learning outcomes. Similar work (e.g., Davidesco & Milne, 2019) has found that student-to-teacher brain synchrony predicted learning in a sequential manner, predominantly in the alpha band. Another study (Dikker et al, 2019) found that pairs of individuals' trait empathy, social closeness, engagement, and social behaviour (e.g., joint action and eye contact) predicted the extent to which their brain activity became synchronized, most prominently in the low alpha (~ 7-10 Hz) and beta frequencies (~ 20-22 Hz).…”
Section: Team-level Eeg Measures Of Cognitionsupporting
confidence: 58%
“…For example, Bevilacqua et al (2019) revealed that students who reported greater social closeness to their teacher showed higher brain-to-brain synchrony with the teacher, and this predicted cognitive learning outcomes. Similar work (e.g., Davidesco & Milne, 2019) has found that student-to-teacher brain synchrony predicted learning in a sequential manner, predominantly in the alpha band. Another study (Dikker et al, 2019) found that pairs of individuals' trait empathy, social closeness, engagement, and social behaviour (e.g., joint action and eye contact) predicted the extent to which their brain activity became synchronized, most prominently in the low alpha (~ 7-10 Hz) and beta frequencies (~ 20-22 Hz).…”
Section: Team-level Eeg Measures Of Cognitionsupporting
confidence: 58%
“…For example, Bevilacqua et al (2019) revealed that students who reported greater social closeness to their teacher showed higher brain-to-brain synchrony with the teacher, and this predicted cognitive learning outcomes. Similar work (e.g., Davidesco & Milne, 2019) has found that student-to-teacher brain synchrony predicted learning in a sequential manner, predominantly in the alpha band. Bevilacqua et al, 2019).…”
Section: The Current State Of the Interdisciplinary Field: Model-derived Eeg Measuressupporting
confidence: 58%
“…For example, students may learn about how acidity is involved in human digestion, and later about ocean acidification ( Davidesco and Milne, 2019 ). Students with greater background knowledge may be more likely to see the connection between how acidity affects both human digestion and ocean life.…”
Section: Learner Abilitiesmentioning
confidence: 99%